Evaluasi Program Sistem Informasi Pengelolaan Keuangan Daerah Berbasis Kinerja - Rochhaeni .; Koesmawan . (Universitas La Tansa Mashiro, 2014)
The purpose of this study was the effectiveness and efficiency of the Financial Management Information System in improving the performance of employees in Lebak. This research includes studies in which the mixture is more to the qualitative approach by including quantitative design. Population 60 government departments in Lebak with the sample used 30 respondents using purposive sampling technique. Analysis qualitative data using software NVivo 10 and Quantitative Analysis using SPSS 20 software. The findings of this study prove that; 1) effectiveness and efficiency of the Financial Management Information System can improve employee performance, 2) the appointment of personnel systems based Lebak administration policies, 3) Training and coaching organized by the Department of Revenue and Fiscal Management given once every year. This shows that the program is conceptually and empirically SIPKD is a program that helps local financial management in order to improve organizational performance or the performance of employees in financial data processing activities.